Inclusion of Intellectually Disabled Children in Early Childhood Education in Hungary in the Light of the Law - Kovács, Krisztina (International Dialogues on Education Journal, 2020)
The study commences with the introduction of the major Hungarian and international tendencies and the legal background of the inclusive education of children with special educational needs in Hungary, then it presents the strategies and tasks of kindergarten teachers in terms of the inclusive kindergarten education of intellectually disabled children, based on the results of our own empirical study. The actuality of the topic is demonstrated by the fact that, according to the statistical data, there is a large number of children with special educational needs in the mainstream kindergartens, which has an impact on the expectations in connection with the professional competence of the kindergarten teachers. According to the 2011 census data, 10% of the Hungarian population is intellectually disabled. The Central Statistics Bureau’s data published in 2018 shows that in 2016, 4.3% of the population belonged to the disabled population. From 2011 to 2016, the number of people with intellectual disabilities increased by 25% and it had exceeded 50,000 people.